1990
DOI: 10.1037/0735-7044.104.3.457
|View full text |Cite
|
Sign up to set email alerts
|

Socially mediated reduction of isolation distress in rat pups is blocked by naltrexone but not by Ro 15-1788.

Abstract: The presence of a single anesthetized littermate significantly reduced the rate of ultrasonic vocalization by 10-day-old pups isolated in a novel environment. Naltrexone (1.0 mg/kg) returned the vocalization rate to the level of pups tested alone and disrupted the maintenance of body contact between the test pup and a companion. This suggests that the companion exerts comforting effects through endogenous opioid mechanisms. Although chlordiazepoxide is as effective as morphine in the quieting of isolation dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 33 publications
2
59
1
2
Order By: Relevance
“…Moreover, opioids are known to have a role in contact quieting [21,23,24,115]. For these reasons, we tested and disproved the hypothesis that the interaction with the dam activates endogenous opioids to regulate the expression of USV potentiation.…”
Section: Opioids Do Not Regulate the Expression Of Potentiationmentioning
confidence: 90%
“…Moreover, opioids are known to have a role in contact quieting [21,23,24,115]. For these reasons, we tested and disproved the hypothesis that the interaction with the dam activates endogenous opioids to regulate the expression of USV potentiation.…”
Section: Opioids Do Not Regulate the Expression Of Potentiationmentioning
confidence: 90%
“…There is also evidence that endogenous opioids mediate mother-infant affiliation in various species (Harris and Newman, 1988;Carden and Hofer, 1990). Recent data reveal brain opioid level changes in MS rats (Ploj et al, 2003a,b) as well as changes in morphine-induced tolerance, physical dependence, and locomotor sensitization (Kalinichev et al, 2001(Kalinichev et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the presence of an anesthetized pup inhibits the emission of isolation-induced USV. The fact that the temperature of the anesthetized pup can be as low as room temperature without losing its potency in reducing calling behaviour again argues against the idea that isolation-induced USV are simply a byproduct of a thermoregulation process [7]. Pharmacological studies showed that quieting in the presence of an anesthetized pup is due to the release of endogenous , n=8).…”
Section: Behavioural Neuroscience · Behavioural Phenotyping · Communimentioning
confidence: 96%